(untitled) (Bangladesh Journal of Nuclear Agriculture, 2025)
Salinity tolerance of three gamma radiation induced mustard mutants (RM-13, RM-14, RM-17) and Binasarisha-11 was evaluated hydroponically at 0, 6, 8, 10 dSm-1. Salinity reduced growth and yield traits but RM-13 and RM-14 showed superior performance, indicating moderate salt tolerance and breeding potential for saline areas of Bangladesh. Bangladesh J. Nuclear Agric, 39(2): 163-168, 2025